Android-based Industrial Internship Management System: Waterfall Development with Dart and Flutter at SMK Negeri 1 West Cikarang - Wibawan, Solahuddin; Faizah, NM; Nurcahyo, Widyat (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
This research presents the development of an Android-based Industrial Internship Management System for the Industrial Electronics Department at SMK Negeri 1 West Cikarang. The study addresses the inefficiencies in manual internship administration by implementing a digital solution using the Waterfall methodology. The application was developed using Dart programming language and Flutter framework to ensure cross-platform compatibility and responsive user interface. The system features include student registration, internship placement tracking, supervisor assignment, performance evaluation, and reporting functionalities. Testing results demonstrate significant improvements in information accessibility, communication efficiency, and administrative workflow. This application effectively bridges the communication gap between students, teachers, and industry partners while streamlining the documentation process. The implementation shows potential for adaptation in similar vocational education settings requiring structured internship management solutions.